The Bioremediation Capacity of Sphingomonas melonis for Methomyl-Contaminated Soil Media: RSM Optimization and Biochemical Assessment by Dreissena polymorpha - onder Erguven, Gokhan; Serdar, Osman; Tanyol, Mehtap; Cikcikoglu Yildirim, Nuran; Yildirim, Numan; Durmus, Barbaros (Wiley-V C H Verlag Gmbh, 2022)
The bioremediation capacity of S. melonis for methomyl investigated with RSM. Oxidative stress and neurotoxic response determined in D. polymorpha. COD and TOC levels were measured. GSH, MDA levels and CAT, SOD, AChE activities in D. polymorpha exposed to before (group A) and after (group B) bioremediated media during 24 and 96 h were tested by using ELISA kit. AchE activity was decreased 24th h but increased during 96th h in group B compared with group A (p<0.05). MDA levels and CAT activities were decreased during 24 h and 96 h in group B compared with group A (p<0.05). GSH levels were increased during 24 h and 96 h in group B compared with group A (p<0.05). SOD activity did not show a significant change in group B (p<0.05). Methomyl could be effectively remediated by S. melonis and CAT, AChE activities and GSH, TBARS levels of D. polymorpha are useful biomarkers for evaluating the bioremediation capacity.
Keywords: methomyl; bioremediation; S; melonis; biochemical assessment; D; Polymorpha